Targeting outcomes redux - Coady, David; Grosh, Margaret; Hoddinott, John F. (International Food Policy Research Institute, 2003)
There are sharply divergent views as to how much narrowly targeted interventions actually benefit the poor. These result from differing assessments of three issues: whether better targeting outcomes are likely to be achieved, whether such methods are cost-effective, and whether the living standards of the poor are improved by such targeted interventions. This paper focuses on the first issue. Using a newly constructed database of targeted interventions, it addresses three questions: (1) What targeting outcomes are observed? (2) Are there systematic differences in targeting performance by targeting methods and other factors? (3) What are the implications for such systematic differences for the design and implementation of targeted interventions?" -- from Authors' Abstract.